Más allá de la conmemoración: la independencia de México de 1821 - Manuel Chust; Joaquín E. Espinosa Aguirre (Caravelle)
2021 represents for Mexico the opportunity to reevaluate the history of its nation state, which emerged two hundred years ago, but also to recover and submit to review ancient characters that have been considered as "consumers", and who, for better or worse, played a prominent role in the later stage of Independence War. This essay offers a short review of the historical production in the bicentenary year organized by academic and governmental institutions, and analyzes as well the official discourse with which the regime carried out the whole pandemic commemoration.